"Common Joys, Sorrows, Adventures, and Struggles": Transnational Encounters in Amy Beach's "Gaelic" Symphony. Issue 2 (18th May 2016) - GERK, SARAH
Abstract: Amy Beach's "Gaelic" Symphony is the most prominent nineteenth-century American expression of Irishness in music. Despite the reference to another country in its title, the work has largely been interpreted via the lens of American nationalism. Its historiography reflects the immense interest in national style in nineteenth-century American music scholarship. This article initiates a discussion about nineteenth-century American composers' engagement with the world beyond their own national borders. It explores the "Gaelic" Symphony's transnational dimensions, which engage largely with two groups: concert music composers and the Irish diaspora. Regarding the former, the article illuminates nuances of intertextuality in Beach's style. It revises the historical narrative surrounding the "Gaelic" Symphony as a response to Antonín Dvořák's "New World" Symphony, finding multiple additional models for Beach's work. The "Gaelic" Symphony is positioned instead as a representation of concert music styles that valued cosmopolitan approaches and judged composers on the skill with which they consciously blended multiple streams of influence. Regarding the latter category of the Irish, the article contextualizes the symphony within a revival of Irish cultural practices taking place in the 1890s, revealing how constructions of Irishness in the symphony reflect Gaelic revival values and respond to social tensions between Boston's Irish-American community and the city's upper class.